Building Customer Loyalty In The Digital Era: The Influence Of Price, Promotion, And Service Quality On Online Food Delivery Applications - Aris Indrajaya Putra As; Alldila Nadhira Ayu Setyaning (International Journal of Economics, Business and Innovation Research, 2024)
This study analyzes the influence of factors that shape customer loyalty on online food delivery service platforms among students of the Faculty of Business and Economics of the Islamic University of Indonesia. The factors studied include consumer purchase intention, price, promotion, information quality, service quality and perceived of usefulness. The PLS-SEM method was used to analyze data from a questionnaire with a sample of 250 respondents. The results of this study show that consumer purchase intention, price, promotion, information quality, service quality and perceived of usefulness are positively significant to customer loyalty. Consumer purchase intention also shows significant positive results on customer loyalty